TOXICITY TEST OF THE MIXED MOUTHWASH OF MAULI BANANA STEM AND BASIL LEAF AGAINST FIBROBLAST CELL STUDY IN VITRO - Martha Vania Saputri; Amy Nindia Carabelly; I Wayan Arya K. Firdaus (FKG Unlam, 2019)
Background: Mauli banana stem and basil leaf are herbal plants which can be used as an herbal mouthwash. People in South Kalimantan often use mauli banana stem to accelerate wound healing because of its antibacterial activity. Basil leaf are proven to inhibit bacterial growth. Mauli banana stem has a bitter taste, so to minimize that bitter taste, basil leaf can be used as a mixture. Basil leaf give fresh and aromatic effect. Extract of mauli banana stem is not toxic against fibroblast cell BHK-21 with 25% concentrate, but there is no research about the toxicity of a mixed mouthwash of mauli banana stem and basil leaf against fibroblast cell BHK-21 yet. Purpose: To analyze IC50 after treatment with a mixed mouthwash of mauli banana stem and basil leaf into the fibroblast cell BHK-21. Method: True experimental using the posttest only with control group design which consisted of 10 treatment groups with several concentrations. Those were 31,25 μg/mL, 62,5 μg/mL, 125 μg/mL, 250 μg/mL, 500 μg/mL, 1000 μg/mL, 2000 μg/mL and 4000 μg/mL. The toxicity test used MTT Assay as a method. This research was formed by 2 stages, which were preparation of fibroblast cell BHK-21 and the toxicity test. The cell viability counted with Freshney formula. Result: The result showed that the IC50 was 2183,43 μg/mL. Conclusion: The mixed mouthwash of mauli banana stem and basil leaf is not toxic against fibroblast cell BHK-21 because IC50 is 2183,43 μg/mL.